Intraspecific plant–soil feedback and intraspecific overyielding in Arabidopsis thaliana - Bukowski, Alexandra R (Blackwell Publishing Ltd, 2014)
Understanding the mechanisms of community coexistence and ecosystem functioning may help to counteract the current biodiversity loss and its potentially harmful consequences. In recent years, plant–soil feedback that can, for example, be caused by below-ground microorganisms has been suggested to play a role in maintaining plant coexistence and to be a potential driver of the positive relationship between plant diversity and ecosystem functioning. Most of the studies addressing these topics have focused on the species level. However, in addition to interspecific interactions, intraspecific interactions might be important for the structure of natural communities. Here, we examine intraspecific coexistence and intraspecific diversity effects using 10 natural accessions of the model species Arabidopsis thaliana (L.) Heynh. We assessed morphological intraspecific diversity by measuring several above- and below-ground traits. We performed a plant–soil feedback experiment that was based on these trait differences between the accessions in order to determine whether A. thaliana experiences feedback at intraspecific level as a result of trait differences. We also experimentally tested the diversity–productivity relationship at intraspecific level. We found strong differences in above- and below-ground traits between the A. thaliana accessions. Overall, plant–soil feedback occurred at intraspecific level. However, accessions differed in the direction and strength of this feedback: Some accessions grew better on their own soils, some on soils from other accessions. Furthermore, we found positive diversity effects within A. thaliana: Accession mixtures produced a higher total above-ground biomass than accession monocultures. Differences between accessions in their feedback response could not be explained by morphological traits. Therefore, we suggest that they might have been caused by accession-specific accumulated soil communities, by root exudates, or by accession-specific resource use based on genetic differences that are not expressed in morphological traits. Synthesis. Our results provide some of the first evidence for intraspecific plant–soil feedback and intraspecific overyielding. These findings may have wider implications for the maintenance of variation within species and the importance of this variation for ecosystem functioning. Our results highlight the need for an increased focus on intraspecific processes in plant diversity research to fully understand the mechanisms of coexistence and ecosystem functioning.